2009
DOI: 10.1016/j.ejpain.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia among physiological overusers with musculoskeletal pain

Abstract: The results of this study point out the need for further elaborating on the concepts of use, overuse and disuse in relation to the fear-avoidance model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(62 reference statements)
0
6
1
2
Order By: Relevance
“…Moreover, more than 60% of the patients in the exercise group were afraid of movement. In contrast, the volunteers in both groups in the present study (those who accepted participating in dance therapy and those who declined to participate) had mean scores on the Tampa Scale of Kinesiophobia indicative of an absence of fear of movement: 39.0±7.08 points (median: 38.5) in the AG and 39.81±6.75 points (median: 42.0) in the CG 24 .…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, more than 60% of the patients in the exercise group were afraid of movement. In contrast, the volunteers in both groups in the present study (those who accepted participating in dance therapy and those who declined to participate) had mean scores on the Tampa Scale of Kinesiophobia indicative of an absence of fear of movement: 39.0±7.08 points (median: 38.5) in the AG and 39.81±6.75 points (median: 42.0) in the CG 24 .…”
Section: Discussioncontrasting
confidence: 58%
“…However, people with CMP often show fear of movement,15 16 which limits the adequate execution of a movement or exercise and leads to more sedentary behaviour 17. Such fear imposes a barrier when exercise is prescribed as part of management resulting in significant clinical implications including reduced adherence to treatment and perseverance of a negative experience with pain 11…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a significant minority interpret pain catastrophically. To date, studies have included either samples of individuals presenting with a specific anatomical site as the primary pain complaint [e.g., only lower back, (Woods and Asmundson, 2008); shoulder, (Andersson and Haldrup, 2003)] or different anatomical sites as the primary pain complaint [e.g., lower back, shoulder, or leg pain; (Lundberg and Styf, 2008;Senlof et al, 2009)], without making comparisons based on the anatomical site of reported pain; however, people with CMP may differ in systematic ways based on the anatomical site of reported pain. Substantial heterogeneity has been identified within samples of patients having disabling CMP (Senlof et al, 2009;Turk and Rudy, 1988), with investigations focusing primarily on within-sample differences in coping strategies (Asmundson et al, 1997;McCracken et al, 1999) or comorbid psychopathology (Hardt et al, 2000;McWilliams et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial heterogeneity has been identified within samples of patients having disabling CMP (Senlof et al, 2009;Turk and Rudy, 1988), with investigations focusing primarily on within-sample differences in coping strategies (Asmundson et al, 1997;McCracken et al, 1999) or comorbid psychopathology (Hardt et al, 2000;McWilliams et al, 2003). To date, studies have included either samples of individuals presenting with a specific anatomical site as the primary pain complaint [e.g., only lower back, (Woods and Asmundson, 2008); shoulder, (Andersson and Haldrup, 2003)] or different anatomical sites as the primary pain complaint [e.g., lower back, shoulder, or leg pain; (Lundberg and Styf, 2008;Senlof et al, 2009)], without making comparisons based on the anatomical site of reported pain; however, people with CMP may differ in systematic ways based on the anatomical site of reported pain. For example, patients with chronic lower back pain (CLBP) may differ from those with chronic upper or lower extremity pain (ULEP) in presentation, recovery trajectory, and pain-related anxiety.…”
Section: Introductionmentioning
confidence: 99%